Reduction of Metal Density of Iron (Fe) and Copper (Cu) Using Corn Active Archarge and Commercial Active Archarge on Water from a Bali Well - Zul Alfian; Fristiwayuni Dara Silvia (Journal of Chemical Natural Resources, 2024)
Through the use of commercial and cassava peel activated charcoal, research was done on how to lower the levels of iron (Fe) and copper (Cu) in well water that had been excavated. X-ray diffraction (XRD) was utilized to conduct the activated charcoal test. The samples were collected from the wells of individuals residing in Kelurahan Sumber Karya Binjai Timur. Water samples were treated with concentrated nitric acid (HNO3) and decomposed. The concentration of iron (Fe) and copper (Cu) was determined before and after adding activated charcoal made from cassava peel and commercially available activated charcoal, with masses of 1, 2, 3, 4, and 5 g. This was done using Atomic Absorption spectrophotometry (AAS) at specific wavelengths of 248.3 nm for Fe and 324.8 nm for Cu. The research findings indicate a decrease in iron (Fe) and copper (Cu) concentration before and after. The amount of activated charcoal made from cassava peel was varied from 1g to 5g. As the mass increased, the iron (Fe) concentration fell by 94.08%, 97.53%, 99.01%, 99.10%, and 99.07% respectively. The copper (Cu) content was reduced by 92.73%, 96.36%, 96.36%, 98.48%, and 97.12%. For commercial activated charcoal with varying masses of 1, 2, 3, 4, and 5 grams, the  concentration of iron (Fe) was reduced by 0.27%, 52.41%, 72.70%, 98.85%, and 98.09%, respectively. The copper (Cu) content reduced by 32.22%, 71.25%, 95.31%, 98.18%, and 96.06%.